Characterization of patients referred for non‐specific intellectual disability testing: the importance of autosomal genes for diagnosis. Issue 4 (15th March 2015) - Tan, C.A.; Topper, S.; del Gaudio, D.; Nelakuditi, V.; Shchelochkov, O.; Nowaczyk, M.J.M.; Zeesman, S.; Brady, L.; Russell, L.; Meeks, N.; Sastry, S.; Arndt, K.; et al.
Abstract : Genetic testing for non‐specific intellectual disability (ID) presents challenges in daily clinical practice. Historically, the focus of the genetic elucidation of non‐specific ID has been on genes on the X chromosome, and recent research has brought attention to the growing contribution of autosomal genes. In addition, next‐generation sequencing (NGS) has greatly improved the ability to simultaneously analyze multiple genetic loci, making large panel testing a practical approach to testing for non‐specific ID. We performed NGS analysis of a total of 90 genes implicated in non‐specific ID. The 90 genes included 56 X‐linked genes and 34 autosomal genes. Pathogenic variants were identified in 11 of 52 (21%) patient samples. Nine of the eleven cases harbored mutations in autosomal genes including AP4B1, STXB1, SYNGAP1, TCF4 and UBE3A . Our mutation‐positive cases provide further evidence supporting the prevalence of autosomal mutations in patients referred for non‐specific ID testing and the utility of their inclusion in multi‐gene panel analysis.